Analysis of mechanical properties and microstructure of multiple die cavity products produced in vertical and horizontal arrangement by gravity die casting - Elfallah, Saleh S Saleh (2012)
Multiple cavities die casting (Permanent die casting )in vertical arrangement and horizontal arrangement moulds are widely used in industry. However, manufacturers assume that each product produced in either arrangement would have the same quality. Manufacturers do not have enough information about the properties of each product, i.e. strength, internal defect and the microstructure. Furthermore, in actuality the quality of each product might be affected. It is the problem that we found within the market now (pinholes, cracks, misruns and etc. ), that is the reason investigation and comparison of the multi product in vertical and horizontal arrangement is needed. This investigation is needed to choose which arrangement is preferred to maintain the quality of the product. The methodology used are vickers microhardness test, izod test, ensile test, density and porosity test and optical microscope inspection for all produced sample. Results of this research show that castings produced at vertical arrangement mould have higher mechanical and properties than castings produced in horizontal arrangement mould. Vertical arrangement castings obtained higher density exceeds %1.6117 than horizontal arrangement castings that ranges between (1.156 and 4.8707 percent ). However, vertical arrangement castings obtained higher porosity exceeds